2021
DOI: 10.1021/acs.chas.0c00105
|View full text |Cite
|
Sign up to set email alerts
|

A Transferable Psychological Evaluation of Virtual Reality Applied to Safety Training in Chemical Manufacturing

Abstract: High-profile accidents in the Chemical sector across research and manufacturing scaleshave provided strong drivers to develop a new benchmark in safety training and compliance. Herein, we describe the design, implementation, and standardized psychological evaluation of virtual reality (VR) applied to process safety training. Through a specific industrial case study, we show that testable learning of complex safetyspecific tasks in VR is statistically equivalent to traditional slidebased video training. Howev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 83 publications
1
17
0
Order By: Relevance
“…Moreover, Dhalmahapatra et al ( 2021) compared the degree of learning level between fully immersive VR and non-immersive VR and their t-test results showed that the safety performance of the users trained in the fully immersive VR was better than the performance of the users trained in the non-immersive VR. On the other hand, researchers such as Beh et al (2021), Joshi et al (2021), Leder et al (2019), Makransky et al (2019), Osti et al (2021), and, Poyade et al (2021, showed in their respective studies that there was no statistical difference on the performance scores between the VR-based training and traditional training methods. Although the results confirmed that there was no statistical difference, four out of six studies stated that performance gained by the VRbased training was higher than using the traditional training method.…”
Section: Does Vr-based Health and Safety Training In Various High-ris...mentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, Dhalmahapatra et al ( 2021) compared the degree of learning level between fully immersive VR and non-immersive VR and their t-test results showed that the safety performance of the users trained in the fully immersive VR was better than the performance of the users trained in the non-immersive VR. On the other hand, researchers such as Beh et al (2021), Joshi et al (2021), Leder et al (2019), Makransky et al (2019), Osti et al (2021), and, Poyade et al (2021, showed in their respective studies that there was no statistical difference on the performance scores between the VR-based training and traditional training methods. Although the results confirmed that there was no statistical difference, four out of six studies stated that performance gained by the VRbased training was higher than using the traditional training method.…”
Section: Does Vr-based Health and Safety Training In Various High-ris...mentioning
confidence: 98%
“…Lastly, some authors (Fig. 2) used VR technologies to train users on both risk assessment and machinery/process operation in construction (Adami et al, 2021;Dhalmahapatra et al, 2021;Le et al, 2015;Nykänen et al, 2020;Sacks et al, 2013), chemical process/laboratory (Makransky et al, 2019;Poyade et al, 2021), manufacturing and assembly (Leder et al, 2019), and mining (Liang et al, 2019) as shown in Fig. 5.…”
Section: What Topics Have Researchers Investigated For Vr-based Healt...mentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the approach, virtual translations of chemistry wet laboratories can demonstrate significant safety considerations without the risk associated with in-person laboratories (e.g., mixing incompatible chemical waste). 26 , 27 In this section, we describe each of these virtual learning categories and highlight some representative works.…”
Section: Virtual Learning Paradigmmentioning
confidence: 99%
“…Thus, digitization methods that allow students to make decisions about reaction conditions show the most potential for retaining the value of synthetic experiments (e.g., DLE, 72 VR, 32 and “labventures” 76 ) and offer some improvements toward safety education as well as material costs. 26 , 27 For more advanced, senior-level laboratories where the goal extends beyond concept familiarity, these options fall short and represent a critical need for future development—particularly in the case of upper-division synthetic experiments.…”
Section: Digitizing Polymer Laboratories For Virtual Environmentmentioning
confidence: 99%